2003
DOI: 10.1002/pi.1121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of poly(methyl methacrylate)/montmorillonite (PMMA/MMT) nanocomposites

Abstract: PMMA/MMT nanocomposites were successfully synthesized via in situ intercalative polymerization, and characterized by means of wide-angle X-ray diffractometry, transmission electron microscopy, thermal gravimetric analysis, dynamic mechanical analysis and Fourier-transform infrared analysis. The nanocomposites possess partially exfoliated and partially intercalated structure, in which the silicate layers are exfoliated into nanometre secondary particles with thickness of less than 20 nm and uniformly dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 15 publications
3
51
1
3
Order By: Relevance
“…It is worth pointing that the increase of storage modulus to nanocomposites confirms high resistance of organoclay against matrix deformation 25,27 . Also, the temperature range of elastic response of nanocomposite is higher than of pure PMMA.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It is worth pointing that the increase of storage modulus to nanocomposites confirms high resistance of organoclay against matrix deformation 25,27 . Also, the temperature range of elastic response of nanocomposite is higher than of pure PMMA.…”
Section: Discussionmentioning
confidence: 71%
“…The Tg then decreases with 5 wt % clay content. It is evident from the Figure 4 that T g were significantly shifted to higher temperature as a function of clay loading 10,25 . Table 1 shows glass transition temperature and molecular weight (M w ) obtained for PMMA and its composites.…”
Section: Damping Factor (Tan δ)mentioning
confidence: 88%
“…This means that the presence of the organoclay leads to more rigid composites and that the organoclay filler limits the mobility of the polymeric chains at the clay-polymer interface, promoting higher resistance of the material against deformation. 14,15 This is a desirable condition for dental composites, that should have intermediate properties for hardness and deforming capacity, approaching the behaviour of the material to the prediction of the Hooke's Law. 15 …”
Section: Dynamical Mechanical Analysis (Dma)mentioning
confidence: 99%
“…14,15 This is a desirable condition for dental composites, that should have intermediate properties for hardness and deforming capacity, approaching the behaviour of the material to the prediction of the Hooke's Law. 15 …”
Section: Dynamical Mechanical Analysis (Dma)mentioning
confidence: 99%
“…Organomontmorillonite (OMMT) is one of the commercial organoclays that has been widely utilized as reinforcing filler in polymer nanocomposites [1][2][3]. Numerous authors have reported on the enhancement in strength and modulus [4][5][6], gas barrier [7] and flame retardant properties [8][9] of polymer/OMMT nanocomposites. In recent years, attention has been devoted to the nanocomposites based on biodegradable polymers and organoclay due to the increasing awareness on the plastic waste pollution.…”
Section: Introductionmentioning
confidence: 99%